Radical Scavenging Activity and Quercetin Content of Muntingia calabura L. Leaves Extracted by Various Ethanol Concentration - Ratih Dyah Pertiwi; Suwaldi; Ronny Martien; Erna Prawita Setyowati (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2020)
Muntingia calabura is broadly cultivated and has become a common roadside tree in Indonesia that is known as